2020
DOI: 10.4103/jehp.jehp_406_20
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of structured feedback for MBBS students: Perception of students and faculty

Abstract: INTRODUCTION: Feedback is an important part of the assessment process. However, one-to-one structured and constructive feedback to the students is not practiced mostly due to lack of practice and feasibility issues. The present study was conducted to understand the perception of students and faculty toward one-to-one structured feedback. METHODOLOGY: All the 3 rd MBBS professional students were included in the study. An orientation was given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Another factor that affected feedback practices was time; clinical teachers expressed not having enough time to give more detailed responses to performance, even though they repeatedly expressed to students that they could be approached at any given time. This is similar to findings of a recent study by Bhattacharyya where time and work constraints were identified as major barriers to giving effective feedback 19 . However, in a study by Al-Hattami most teachers and students did not see that time, feasibility, amotivation or uncaring attitude towards students could be deemed a barrier to not providing constructive feedback 20 .…”
Section: Discussionsupporting
confidence: 90%
“…Another factor that affected feedback practices was time; clinical teachers expressed not having enough time to give more detailed responses to performance, even though they repeatedly expressed to students that they could be approached at any given time. This is similar to findings of a recent study by Bhattacharyya where time and work constraints were identified as major barriers to giving effective feedback 19 . However, in a study by Al-Hattami most teachers and students did not see that time, feasibility, amotivation or uncaring attitude towards students could be deemed a barrier to not providing constructive feedback 20 .…”
Section: Discussionsupporting
confidence: 90%
“…According to a research, feedback content has the potential to enhance mini-CEX's usefulness as an assessment tool and provide both constructive and critical feedback [ 29 ]. Positive feedback about the use of mini-CEX in many areas of medical education has been received by numerous other researchers [ 4 , 21 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, constructive feedback from both the assessor and the student has been shown to have an impact on a student’s education [ 30 ]. Thus, mini‑CEX supports feedback which can improve the performances of the trainee, though leniency of assessors might limit the identification of trainees who underperform [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the positive responses received from both students and faculty highlight that the students are receptive to feedback, provided it is structured, constructive, and helps them to achieve their learning goals. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%